De novo Portal Vein Thrombosis in Non-Cirrhotic Non-Alcoholic Fatty Liver Disease: A 9-Year Prospective Cohort Study - Abdel-Razik, Ahmed; Mousa, Nasser; Shabana, Walaa; Yassen, Ahmed H.; Abdelsalam, Mostafa; Wahba, Mohamed M.; Helmy, Eman Mohamed; Tawfik, Ahmed M.; Zalata, Khaled; Hasan, Ahmad S.; Elhelaly, Rania; Elzehery, Rasha; et al. (Frontiers in Medicine, 2021)
Background and Aims: Approximately 30–40% of portal vein thrombosis (PVT) remains of unknown origin. The association between non-alcoholic fatty liver disease (NAFLD) and PVT is a matter of debate. This study aimed to investigate the association between PVT and NAFLD. Methods: We included 94 out of 105 consecutive NAFLD patients in this prospective cohort study in addition to 94 from the healthy control group. We evaluated biochemical, clinical, immunological, and histopathological parameters; waist circumference (WC); leptin; adiponectin; and leptin/adiponectin ratio (LAR) for all participants at baseline and every 3 years thereafter. We described the characteristics of participants at baseline and showed individual WC, LAR, and PVT characteristics. Potential parameters to predict PVT development within 9 years were determined. Results: PVT developed in eight (8.5%) patients, mainly in the portal trunk. Univariate analysis showed three PVT-associated factors: diabetes mellitus (P = 0.013), WC (P < 0.001), and LAR (P = 0.002). After adjusting multiple confounding variables, the multivariate model showed that the only significant variables were WC and LAR. By applying the receiver operating characteristic curve, WC had 98.8% specificity, 87.5% sensitivity, and 0.894 area under the curve (AUC) for prediction of PVT (P < 0.001) at cutoff values of > 105 cm. In comparison, LAR had 60.5% specificity, 87.5% sensitivity, and 0.805 AUC for PVT prediction (P < 0.001) at cutoff values of >7.5. Conclusions: This study suggests that increased central obesity and LAR were independently associated with PVT development in non-cirrhotic NAFLD patients, and they should be considered risk factors that may participate in PVT multifactorial pathogenesis.